2019
DOI: 10.1016/j.jnucmat.2019.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Creep and damage anisotropies of 9%Cr and 14%Cr ODS steel cladding

Abstract: Two Oxide Dispersion Strengthened (ODS) steel tubes, obtained by means of hot extrusion and cold rolling, are studied as potential materials for cladding applications in sodium-cooled fast reactors. A 9%Cr martensitic tube (Fe-9Cr-1W-0.3Ti-0.25Y2O3) with isotropic microstructure is compared to a 14%Cr ferritic tube (Fe-14Cr-1W-0.3Ti-0.25Y2O3) with elongated grains and a strong texture. Tile and notched ring specimens are used to perform uniaxial creep tests at 650°C in the longitudinal and transverse direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Fig. 7 shows a comparison of the high-temperature creep performance and radiation resistance between ODS and RAFM steels in recent years [100][101][102][103]. The creep life of the 9Cr ODS steel is ~1000 times longer than that of the F82H and Eurofer 97 steels under 650°C/130 MPa.…”
Section: Oxide Dispersion-strengthened (Ods) Steelmentioning
confidence: 99%
“…Fig. 7 shows a comparison of the high-temperature creep performance and radiation resistance between ODS and RAFM steels in recent years [100][101][102][103]. The creep life of the 9Cr ODS steel is ~1000 times longer than that of the F82H and Eurofer 97 steels under 650°C/130 MPa.…”
Section: Oxide Dispersion-strengthened (Ods) Steelmentioning
confidence: 99%
“…The high density of nanoscale oxides provides ODS steels with excellent mechanical performance by blocking dislocation slipping and hindering grain boundaries movement [ 5 , 6 , 7 , 8 , 9 ]. Several studies have reported that fine and thermo-stable oxides improve the creep resistance of ferritic steels [ 10 , 11 , 12 , 13 ] and trap He in fine bubbles, thereby limiting He movement and restraining He brittleness [ 2 , 3 , 4 ]. The common processes to fabricate ODS steels are powder metallurgy (PM) with mechanical alloying (MA) and heat consolidation [ 14 ], including hot isostatic pressure (HIP) [ 9 ], hot extrusion (HE) [ 15 , 16 ], and spark plasma sintering (SPS) [ 17 ], and ODS steels have a high density and an excellent tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ODS steel microstructures are known to be very anisotropic, which depends on the used manufacturing and forming processes [13]. Thus, creep results are very dependent on both the microstructure and testing direction [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, ODS-materials lose their creep strength when melted, which must be taken into account when designing the test set-up. Rather little openly available information on ODS tube material internal pressure tests and plugging techniques was found in literature [18], [15]. Different methods for plugging have been prospected in earlier study [19].…”
Section: Introductionmentioning
confidence: 99%